21st Century Skills Development in Modern Pesantren - Aghni Zakiatun Nabila; Ahmad Farid; Siti Zuflihatul Magfiroh; Nur Zhafirah Hafizhah; Maulida Nisaul Khomsah (Yayasan Adra Karima Hubbi, 2024)
Background: The integration of 21st-century skills into educational systems is crucial for preparing students for the global era. Modern Islamic boarding schools (pesantren) in Indonesia face the challenge of balancing traditional Islamic education with contemporary skill development. Purpose: This study aims to examine the implementation of 21st-century skills development in modern pesantren, identify challenges, and explore effective strategies for integration. Method: A qualitative case study approach was employed, involving three modern pesantren in Java. Data were collected through in-depth interviews, participant observation, document analysis, and focus group discussions. Thematic analysis was used to interpret the data. Results: Modern pesantren have implemented various programs to develop critical thinking, creativity, communication, collaboration, and digital literacy skills. However, they face challenges including limited resources, resistance to change, and concerns about preserving traditional values. Effective strategies identified include integrated curriculum development, teacher training, external partnerships, mentoring programs, and judicious use of technology. Conclusion: Modern pesantren demonstrate significant potential in integrating 21st-century skills while maintaining their core Islamic values. The study recommends collaborative efforts among pesantren, government, researchers, and the community to support this educational transformation and enhance the relevance of pesantren education in the global era.